Amino Acid‐Induced Interface Charge Engineering Enables Highly Reversible Zn Anode. (6th August 2021) - Lu, Haotian; Zhang, Xuanlin; Luo, Minghe; Cao, Keshuang; Lu, Yunhao; Xu, Ben Bin; Pan, Hongge; Tao, Kai; Jiang, Yinzhu
Abstract: Despite the impressive merits of low‐cost and high‐safety electrochemical energy storage for aqueous zinc ion batteries, researchers have long struggled against the unresolved issues of dendrite growth and the side reactions of zinc metal anodes. Herein, a new strategy of zinc‐electrolyte interface charge engineering induced by amino acid additives is demonstrated for highly reversible zinc plating/stripping. Through electrostatic preferential absorption of positively charged arginine molecules on the surface of the zinc metal anode, a self‐adaptive zinc‐electrolyte interface is established for the inhibition of water adsorption/hydrogen evolution and the guidance of uniform zinc deposition. Consequently, an ultra‐long stable cycling up to 2200 h at a high current density of 5 mA cm −2 is achieved under an areal capacity of 4 mAh cm −2 . Even cycled at an ultra‐high current density of 10 mA cm −2, 900 h‐long stable cycling is still demonstrated, demonstrating the reliable self‐adaptive feature of the zinc‐electrolyte interface. This work provides a new perspective of interface charge engineering in realizing highly reversible bulk zinc anode that can prompt its practical application in aqueous rechargeable zinc batteries. Abstract : Although aqueous rechargeable zinc batteries holds great promise in energy storage, dendrite growth and side reactions have long limited the advance of zinc metal anode in rechargeable zinc battery. Herein, an interface charge engineering strategy is proposed via an amino acid additive to regulate zinc‐electrolyte interface charge states and achieve a highly reversible Zn plating/stripping process.